Unveiling purine metabolism dysregulation orchestrated immunosuppression in advanced pancreatic cancer and concentrating on the central role of NT5E - Zhang, Junqian; Zhang, Xiaobo; Wu, Ruixin; Dong, Chang-Sheng (Frontiers in Immunology, 2025)
BackgroundThe dismal efficacy of immunotherapy for Pancreatic cancer (PC) can be predominantly ascribed to its distinctive cold-tumor properties. The by-products of purine metabolic reprogramming are extensively engaged in tumor immune modulation, influencing the functions and recruitment of immune cells and molding an immune microenvironment that is propitious for tumor growth.MethodsWe harnessed single-cell transcriptomics and spatial transcriptomics to concurrently analyze the purine metabolism (PM) features of the PC microenvironment. We quantitatively appraised the PM traits of diverse cell subsets via scoring algorithms such as AUCell and Ucell. Moreover, cell development and cell-cell interaction analysis elucidated the alterations in TME induced by PM dysregulation. Additionally, we defined the PM disorder characteristics of PC patients and utilized this to assess the immune phenotypes and prognoses of the patient population. Also, we identified the crucial intermediate genes that impact PM reprogramming and the establishment of an immunosuppressive environment within the TME of PC, and validated them through spatial sectioning and cell co-culture experiments.ResultsMulti - dimensional transcriptome data elucidated the unique heterogeneity of PM in the PC microenvironment, which manifested that tumor cells and fibroblasts demonstrating higher PM scores in the TME. Cellchat analysis revealed that malignant cells with elevated PM expression were concomitantly associated with frequent interactions with CAFs as well as high expression of ligand-receptor pairs and transcription factors. Spatial data further corroborated this finding. Furthermore, the newly constructed PM disorder criteria indicated that patients with high PM levels were associated with a lack of response to immunotherapy and an immunosuppressive microenvironment. Finally, this study identified the singular role of NT5E in the immunosuppression resulting from PM reprogramming in PC. CCK8 and invasion experiments following the co-culture model demonstrated that intervention targeting NT5E could reverse the augmented malignancy of PC induced by co-cultured CAFs. NT5E is potentially a key target for reversing the “stiff-cancer” characteristics of PC.ConclusionThis study demonstrates that PM metabolic disorders could impinge upon tumor immunotherapy and exacerbate the immunosuppression engendered by the progression of PC fibrosis. Therapeutic strategies targeting PM or NT5E may offer a ray of hope for patients with advanced PDAC.